Characterization of the thermoresponsive shape‐memory effect in poly(ether ether ketone) (PEEK). Issue 3 (12th September 2013) - Wu, Xue Lian; Huang, Wei Min; Ding, Zhen; Tan, Hui Xin; Yang, Wen Guang; Sun, Ke Yuan
ABSTRACT We conducted a systematic experimental investigation to characterize the shape‐memory effect in a commercial poly(ether ether ketone) (PEEK), which is a very important high‐temperature polymers at present. The focus was on the influence of the programming conditions and heating temperature for recovery on the shape‐recovery ratio (Rr). We concluded that PEEK is not only an important engineering polymer as it is traditionally known but is also an excellent high‐temperature shape‐memory polymer. For a residual programming strain of 30%, the maximum Rr was about 90%. It was revealed that it was practically feasible to program PEEK at room temperature and to lower the recovery temperature from its melting temperature range to around its glass‐transition temperature. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39844.